Addressing public health emergencies via Facebook surveys: Advantages, challenges, and practical considerations - Grow, A; Perrotta, D; Del Fava, E; Cimentada, J; Rampazzo, F; Gil-Clavel, S; Zagheni, E (JMIR Publications, 2020)
Surveys of the general population can provide crucial information for designing effective nonpharmaceutical interventions to tackle public health emergencies, such as the COVID-19 pandemic. Yet, conducting such surveys can be difficult, especially when timely data collection is required. In this viewpoint paper, we discuss our experiences with using targeted Facebook advertising campaigns to address these difficulties in relation to the COVID-19 pandemic. We describe central advantages, challenges, and practical considerations. This includes a discussion of potential sources of bias and how they can be addressed.